(untitled) (Medical Forum Monthly, 2024)
Objective: To comparison of two methods of semen preparation for subsequently improving IUI success rates in couples with mild male-factor infertility: density gradient centrifugation and swim-up. Study Design: A cross sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology District Head Quarter Teaching Hospital Swabi from January 2022 to December 2022. Methods: 120 patients with mild male factor infertility, IUI was performed after semen preparation. The patients were then randomized to density gradient centrifugation or swim-up method. Sperm motility, morphological characteristics, and concentration of sperm were major clinical assessment done. Pregnancy rates derived from the two methods were statistically compared using analysis of variance with p < 0.05 as the level of significance. Results: Of the 120 patients, 24 patients in the density gradient group achieved pregnancy rate of 18 + 3.5 per cent compared to 13 patients in the swim-up group with pregnancy rate of 10 + 2.8 per cent with significant difference (p < 0.05). Motility and morphology become enhanced in density gradient group reflected in greater IUI outcomes. Improved sperms quality especially motility at the beginning of the treatment also presented significant positive correlation with outcomes in the study. Conclusion: IUI pregnancy rates were higher with density gradient centrifugation than swim-up in mild male factor infertility cases because of improved motility and morphological quality. These results suggest that the choice of the best eviction method plays a critical role in the success of IUI.